Boris Vian's American Movie: The Lost Authorship of I Will Spit on Your Graves - M. Martin Guiney (Studies in 20th & 21st Century Literature, 2002)
Boris Vian (1920-1959) is today considered one of France's foremost avant-garde novelists of the twentieth century, but in his lifetime he was known to a wide audience as the author of one work: J'irai cracher sur vos tombes (I Will Spit on Your Graves), a pastiche of American hard-boiled fiction which he published in 1946 under the name of a fictitious Black American author, Vernon Sullivan. Vian died twelve years later of heart failure while viewing the film adaptation, which he had no part in producing. Vian-as-author "died" long before that fateful moment, however: first when he perpetrated a hoax, claiming to be the book's translator, not its author; and then by exploiting the commercial potential of American pulp fiction for his own financial benefit (the book became the best-selling novel in France in 1947, and made Vian wealthy). Over the course of his literary career, he repeatedly tried to reclaim his novel as legitimate political commentary and "art." The saga of J'irai is one of conflict: between print and film, art and commerce, native and foreign; it ultimately reveals the profound, quasi-masochistic ambivalence of the French public towards the "americanization" of culture.
Keywords: Boris Vian; France; avant-garde; avant-garde novelists; twentieth century; J' irai cracher sur vos tombes; I Will Spit on Your Graves; American; 1946; Black American author; Vernon Sullivan; American pulp fiction; art; political commentary; J' irai; masochistic ambivalence; Americanization